Genetic Diversity of Boeseman's Rainbowfish (Melanotaenia Boesemani) Reared in Indonesian Farms Compared to Endangered Natural Populations. (September 2015) - Nugraha, Media Fitri Isma; Pouyaud, Laurent; Carman, Odang; Widyastuti, Utut; Junior, Muhammad Zairin; Kadarusman,; Avarre, Jean-Christophe
Endemic to two lakes (Ayamaru and Uter) of West Papua (Indonesia), the Boeseman's Rainbowfish Melanotaenia boesemani Allen & Cross, 1980 is a very popular ornamental freshwater fish. As a result, this rainbowfish species faces great threats and is on the red list of endangered species. Therefore, rearing of this species in aquaculture systems appears to be a promising solution to limit capture of wild specimens and prevent its extinction. Although its reproduction cycle has been controlled for more than 30 years, very few farms still raise M. boesmani, probably due to the problems reported by the farmers, such as decline of production, higher proportion of females per spawning, loss of coloration, lower growth rate and fecundity. Using 12 microsatellites previously developed for this species, comparison of genotypes within six farms around Jakarta indicated that all reared strains originated from Ayamaru Lake. No deficit in heterozygotes was evidenced, suggesting that there was no major inbreeding in these reared populations. Genotype analysis also suggested that M. boesemani species is a metapopulation composed of genetically differentiated populations. Altogether, these results indicate that the problems experienced by the farmers are due not to inbreeding depression but to other factors such as inadequate management and/or poor water quality. Yet, increasing aquaculture production is probably the most effective way to alleviate the pressure that M. boesemani faces in its natural environment.